Interventional Protocol for Treatment of Complications after Esophagojejunostomy for Esophagogastric Carcinoma. (1st December 2019) - Bi, Yonghua; Li, Jindong; Yi, Mengfei; Yu, Zepeng; Han, Xinwei; Ren, Jianzhuang
Abstract : Background . Anastomotic stenosis and leakage are rare complications after esophagojejunostomy. The management of complications after esophagojejunostomy remains a challenge. We evaluated the outcomes and clinical effectiveness of an alternative interventional protocol. Objectives . To determine the safety and efficacy of interventional treatment for the management of complications after esophagojejunostomy. Methods . This study included 24 consecutive patients with complications after esophagojejunostomy treated using interventional protocol. Patients received balloon dilation or stenting for anastomotic stenosis. Patients with anastomotic leakage received three-tube placement or retrievable covered esophageal stent placement, followed by abscess drainage, nutritional support, and anti-inflammatory treatment. The three tubes and esophageal stents were removed after leakage healing and stenosis ceased. Results . Thirteen patients received three-tube method, and 16 patients received covered stent placement. All procedures were technically successful, except for a failure of Y-type esophageal stent placement in one patient. The median retention time of stent and abscess drainage tube was 67.5 days and 87 days, respectively. No perioperative death, esophageal rupture, or massive hemorrhage was found during procedures. During follow-up, 14 patients died of cancer recurrence, and one died of severe pulmonary infection. The 1-, 3-, 5-year survival rates were 39.5%, 23.7%, and 23.7%, respectively. Conclusion . Interventional protocol is safe, feasible, and efficacious for treatment of complications after esophagojejunostomy.